Perceived emotional demands-abilities fit - Diefendorff, James M. (Institutional Knowledge at Singapore Management University, 2016)
The purposes of this paper are to introduce the concept of perceived emotional demands-abilities (ED-A) fit and develop theory about how it relates to other fit perceptions as well as employee well-being and performance outcomes. ED-A fit is defined as the perceived congruence or match between the emotional demands of the job and one's abilities to meet those demands. In two studies using occupationally diverse samples from Western and Eastern cultures, we empirically distinguished perceived ED-A fit from other fit perceptions (i.e. person-organisation, demands-abilities, needs-supplies, person-group, person-supervisor). In addition, across the two studies, we found that perceived ED-A fit accounted for incremental variance in job satisfaction, work tension, felt inauthenticity, burnout, self and supervisor ratings of job performance, and psychological need satisfaction, controlling for the effects of other fit perceptions.